Relationship between soil morphology and variability of upland degradation in Bogowonto Watershed, Central Java, Indonesia - Krishna Aji; Azwar Maas; Makruf Nurudin (Brawijaya University, 2020)
Land-use change and lack of conservation in Bogowonto Watershed area have caused land degradation due to erosion and landslides. The rate of land degradation can be measured through the morphological characteristics of the soil and landscape. This study aimed to identify the relationship between the morphological characteristics of the soil and the rate of land degradation in Bogowonto Watershed area. The research framework initiated from the interpretation of thematic maps, surveys and field observations, and verification using land degradation assessment software. Sample points were determined using a stratified random sampling method. In general, land degradation is affected by slope, limited soil development, suboptimal conservation measures, and land-use change. Particularly, land degradation is affected by the type of landscape and the morphological characteristics of the soil. Volcanic hilly landscapes show a degradation rate of fine to very fine, characterized by thick soil depth (>60 cm), generous root distribution, loamy textured soil, fine soil particle size (Ø <0.002 mm), and good soil structure. The distribution of easily weathered volcanic ash causes volcanic hills to have thick and fertile soil characteristics. Quaternary-tertiary volcanic transition landscapes show a degradation rate of damaged to heavily damaged, characterized by thin soil depth (<60 cm), limited rooting, dominant coarse fraction (Ø 2–0.05 mm), and contact with fields lithological discontinuity. The data obtained provide information on the morphological characteristics of the soil and land degradation in Bogowonto Watershed area. The results of the study can also be used as a formulation for the conservation of Bogowonto Watershed area.